2016
DOI: 10.3389/fphar.2016.00502
|View full text |Cite
|
Sign up to set email alerts
|

Development of an IgY Antibody-Based Immunoassay for the Screening of the CYP2E1 Inhibitor/Enhancer from Herbal Medicines

Abstract: Cytochrome P450 (CYP) 2E1 is an important enzyme involved in the metabolism of many endogenous and exogenous compounds. It is essential to evaluate the expression of CYP2E1 in the studies of drug–drug interactions and the screening of drugs, natural products, and foodstuffs. The present work is a feasibility study on the development of immunoassays using a specific and sensitive chicken-sourced anti-CYP2E1 IgY antibody. Cloning, expression, and purification of a recombinant CYP2E1 (mice origin) protein were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…As previous studies reported, CYP2E1 and CYP2C9 play a vital role in the metabolism of many drugs (He et al 2009;Lim et al 2014;Xu et al 2017;Bedada and Neerati 2018). There are also many drugs inhibiting the activity of CYP2E1 and CYP2C9 (Pan et al 2010;Jiang et al 2016;Liu et al 2017;Hao et al 2018), and we get similar results in the study of CEP. Different from CYP3A4, the activity of human liver microsomal CYP2E1 and CYP2C9 was inhibited by CEP competitively.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As previous studies reported, CYP2E1 and CYP2C9 play a vital role in the metabolism of many drugs (He et al 2009;Lim et al 2014;Xu et al 2017;Bedada and Neerati 2018). There are also many drugs inhibiting the activity of CYP2E1 and CYP2C9 (Pan et al 2010;Jiang et al 2016;Liu et al 2017;Hao et al 2018), and we get similar results in the study of CEP. Different from CYP3A4, the activity of human liver microsomal CYP2E1 and CYP2C9 was inhibited by CEP competitively.…”
Section: Discussionsupporting
confidence: 82%
“…According to previous studies about the pharmacokinetic profiles of CEP in rats, the plasma C max values of CEP in orally administered with CEP (10 mg/kg) were approximately 0.05 lg/ mL (Jiang et al 2016), which is much lower than the Ki and IC 50 values of CEP. Consequently, the drug-drug interaction might not occur when CEP was co-administered with the substrates of the CYP3A4, CYP2E1 and CYP2C9.…”
Section: Discussionmentioning
confidence: 93%
“…CYP2E1 metabolizes a wide variety of chemicals with different structures, in particular small and hydrophobic compounds, including potential cytotoxic and carcinogenic agents. Anti-CYP2E1 IgY was specific, without reacting with other cytochromes, and was able to detect the reduction of hepatic CYPE2E1 expression due to the ingestion of natural products with hepatoprotective effects [120].…”
Section: Enzyme Detectionmentioning
confidence: 99%
“…There is a wide range of benefits of IgY antibody. Immunoglobulin Y (IgY) and the functional counterpart of mammalian IgG are excellent candidates alternatively to antibiotics for preventive and therapeutic against bacteria and virus [ 109 , 110 ]. IgY is also effective in providing protection against a wide range of gastrointestinal pathogens in humans and animals.…”
Section: Alternative Methods For Animal Husbandrymentioning
confidence: 99%